2012
DOI: 10.1007/s00415-012-6785-y
|View full text |Cite
|
Sign up to set email alerts
|

Historical changes of seasonal differences in the frequency of multiple sclerosis clinical attacks: a multicenter study

Abstract: Previous papers show discordant patterns of monthly and seasonal differences in the frequency of multiple sclerosis relapses. Attacks are more often reported in spring and summer, but there are many variations, mainly as to summer peaks. This paper, an MSBase collaboration substudy, reports multiple series of relapses from 1980 to 2010, comparing ultradecennal trends of seasonal frequency of attacks in different countries. The MSBase international database was searched for relapses in series recording patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Relapse rates vary according to season, 13 with peaks in early winter and summer; thus rapid-access clinic demand may fluctuate throughout the year and capacity should allow for this. Clinicians require adequate time to cover the wide range of issues arising in the context of an acute deterioration in MS (see below); our own rapid access has 40-min clinic slots.…”
Section: Service Model Considerationsmentioning
confidence: 99%
“…Relapse rates vary according to season, 13 with peaks in early winter and summer; thus rapid-access clinic demand may fluctuate throughout the year and capacity should allow for this. Clinicians require adequate time to cover the wide range of issues arising in the context of an acute deterioration in MS (see below); our own rapid access has 40-min clinic slots.…”
Section: Service Model Considerationsmentioning
confidence: 99%
“…Studies from several smaller patient cohorts showed variable results, some reporting a spring [26] and other earlier works reporting a summer peak [27,28] of relapse incidence ( table 1 ). A hypothesis was proposed that the seasonality of the peak relapse incidence may show a long-term trend towards phaseshift [29] , but this view requires further validation.…”
Section: Epidemiology Of Ms Relapsesmentioning
confidence: 99%
“…However, a large amount of permafrost with high thermal sensitivity in these areas would bring great potential dangers to railway transportation [3][4][5][6][7][8][9]. Geophysical data can provide important information to detect the permafrost [10][11][12]. Hence, identifying the geological conditions of the railway subgrade and locating the permafrost are crucial for the railway construction in Western China.…”
Section: Introductionmentioning
confidence: 99%